Towards a community-wide effort for benchmarking in subsurface hydrological inversion: benchmarking cases, high-fidelity reference solutions, procedure, and first comparison - T. Xu; S. Xiao; S. Reuschen; N. Wildt; H.-J. Hendricks Franssen; H.-J. Hendricks Franssen; W. Nowak (Hydrology and Earth System Sciences)
Inversion in subsurface hydrology refers to estimating spatial distributions of (typically hydraulic) properties often associated with quantified uncertainty. Many methods are available, each characterized by a set of assumptions, approximations, and numerical implementations. Only a few intercomparison studies have been performed (in the remote past) amongst different approaches (e.g., Zimmerman et al., 1998; Hendricks Franssen et al., 2009). These intercomparisons guarantee broad participation to push forward research efforts of the entire subsurface hydrological inversion community. However, from past studies until now, comparisons have been made among approximate methods without firm reference solutions. Note that the reference solutions are the best possible solutions with the best estimate and posterior standard deviation and so forth. Without reference solutions, one can only compare competing best estimates and their associated uncertainties in an intercomparison sense, and absolute statements on accuracy are unreachable.